The Effect of Authentic Leadership on Psychological Capital, Work Engagement, and Innovative Behavior - Melati Kusuma Wardhani; Lia Amalia (Journal of Social Research, 2026)
This study aims to analyze the effect of authentic leadership on psychological capital, work engagement, and innovative behavior among employees in service-based startup companies in Indonesia. In addition, this study examines the mediating role of psychological capital in the relationship between authentic leadership and work engagement, as well as the mediating role of work engagement in the relationship between authentic leadership and innovative behavior. This research uses a quantitative approach with a survey method involving 140 employees selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results show that authentic leadership has a positive and significant effect on psychological capital and work engagement. Psychological capital also has a significant positive effect on work engagement and acts as a partial mediator in the relationship between authentic leadership and work engagement. Furthermore, work engagement has a strong positive effect on innovative behavior and mediates the relationship between authentic leadership and innovative behavior. These findings indicate that authentic leadership plays a strategic role in enhancing employees’ psychological conditions and engagement, which in turn fosters innovative behavior. This study contributes to the development of human resource management and organizational behavior literature, particularly in the context of dynamic startup environments.